Boosting Manufacturing Firms' Exports? The role of trade facilitation in Africa - Ruth Hoekstra (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2013)
Facilitating trade is essential for Africa's economic development and further integration into the world economy, as business in Africa still suffers from behind-the-border barriers to trade. Using firm level data from the World Bank's Enterprise surveys covering more than 6,500 manufacturing firms, this paper empirically investigates the determinants of African firms' export decisions with a special focus on trade facilitation measures like the energy or telecommunications infrastructure. Overall, trade facilitation can increase African firms' probability to participate in international trade. Furthermore, lower trade barriers are associated with a higher propensity to export, i.e. stimulate the growth of exports.
Keywords: F13; F15; O24; 380; Trade facilitation; Trade barriers; Africa; Firm-level data; Export probability; Handelsliberalisierung; Exportwirtschaft; Industrie; Afrika